Video self-modelling: an intervention for children with behavioural difficulties. Issue 1 (2nd January 2017) - Regan, Helen; Howe, Julia
Abstract: There has recently been a growth in interest in the use of video technology in the practice of educational psychologists. This research explores the effects of a video self-modelling (VSM) intervention on the behaviours of a child in mainstream education using a single case study design set within a behaviourist paradigm. VSM is a behavioural intervention that requires the participant, in this instance a six year old boy, to view a short video of himself engaging in target behaviours. Baseline and post-intervention data were collected through classroom-based observations by the researcher in order to monitor the frequencies of the target behaviours and to evaluate the effectiveness of the VSM intervention. The participant demonstrated higher frequencies of target behaviours following the intervention. The results suggest that VSM is a promising method for educational psychologists to use as a proactive approach with pupils in educational settings to improve target behaviours.